Informatization, Digitalization, and Intellectualization: Which Integration Mode Will Determine the Development of Strategic Emerging Industries? - Shenghua Zheng; Haijie Chen (SAGE Open)
From the perspective of theoretical integration, this paper utilizes the theories of informatization, digitization, intellectualization, and industrial integration to address two theoretical gaps. First, it seeks to elucidate their similarities and differences by comparing the connotations, technical characteristics, and operational mechanisms of informatization, digitization, and intellectualization while uncovering their iterative evolution relationship from lower to higher levels. Second, it evaluates the potential of informatization, digitization, and intellectualization in terms of technical communities, integration capabilities, and system architectures, thereby demonstrating that intelligent integration constitutes the most promising enabling model for strategic emerging industries. This study establishes a theoretical foundation for intelligent integration in strategic emerging industries. At the same time, positioning intellectualization as a higher-order enabler than digitalization helps governments design scientifically guided development plans to mitigate the risks of policy stagnation in the “digital trap.”